Characteristics of electrochemical hydrogen storage using Ti–Fe based alloys prepared by ball milling. (5th January 2022) - Shang, Hongwei; Zhang, Yanghuan; Gao, Jinliang; Zhang, Wei; Wei, Xin; Yuan, Zeming; Li, Yaqin
Abstract: In this paper, the TiFe-based master alloy Ti1.04 Fe0.7 Ni0.1 Zr0.1 Mn0.1 Pr0.06 was fabricated by conventional induction melting with high purity helium as the protective gas. After that, the as-cast specimens were mechanically milled with nickel powders to synthesize the as-milled Ti1.04 Fe0.7 Ni0.1 Zr0.1 Mn0.1 Pr0.06 + 10 wt.% Ni composites with excellent electrochemical characteristics. The master alloy is composed of TiFe, Ti2 Fe and Pr phases, which has a typical crystal structure. Mechanically milling the master alloy with nickel powder leads to the reductions of the grain size and particle size, even forming amorphous structure. The experimental results showed that the specimens after ball-milling treatment can be used to hydriding and dehydriding by electrochemistry, getting the maximal discharge capacity in the first cycle, and no activation was required. The discharge capacity of the as-milled composites declined from 264.2 to 133.6 mAh/g with the milling duration extending from 5 to 30 h. The electrochemical kinetics markedly declined with prolonging milling duration. However, the electrochemical cycling stability of the specimens reduced firstly and then increased with the prolongation of grinding duration. Highlights: The ferrotitanium alloy +10 wt.% Ni were prepared by mechanical milling. The as-milled (5 h) specimen has the maximal discharge capacity of 264.2 mAh/g. The electrochemical kinetics are worse with the prolongation of milling duration.